Proceso de atención nutricional en el paciente masculino de 42 años de edad con VIH – Sida y bajo peso. - Avilés Sevillano, Teresa Analía (2022)
HIV (human immunodeficiency syndrome), is considered one of the most common diseases in the population worldwide, eating disorders caused by this virus considerably affect the human being, which produces a great weight loss. Good nutrition cannot cure AIDS or prevent HIV infection, but it can help maintain and improve the nutritional status of a person with HIV/AIDS and slow the progression of HIV to AIDS-related illnesses. Nutritional care and support are important from the early stages of infection to prevent nutritional deficiencies from developing. Eating well helps maintain and improve the functioning of the immune system - the body's protection system against infection - and therefore helps a person stay healthy. Many of the pathological conditions related to HIV/AIDS affect food intake, digestion and assimilation, while others influence the functions of the organism. Many of the symptoms of this condition (for example, diarrhea, weight loss, inflammation of the mouth and sore throat, nausea or vomiting) can be treated with proper nutrition. Good nutrition will complement and enhance the effect of any medications that are taken. This clinical case exposes the food needs of a person affected by HIV/AIDS and recommendations are made on eating habits to cover those needs. It also explains how to deal with the nutritional aspects of HIV-related health conditions.